Rh(II)-catalyzed intramolecular N-H insertion of D-glucose-derived delta-amino alpha-diazo beta-ketoester: Synthesis of pyrrolidine iminosugars - Vyavahare, Vinod P.; Chattopadhyay, Subrata; Puranik, Vedavati G.; Dhavale, Dilip D. (Synlett, 2007)
The rhodium acetate catalyzed reaction of D-glucose-derived delta-amino alpha-diazo beta-ketoester allows a stereoselective beta-facial intramolecular N-H insertion reaction that leads to formation of the bicyclic pyrrolidinone ring skeleton in high yield. The sugar-substituted pyrrolidinone thus obtained was elaborated to allow the synthesis of promising glycosidase inhibitors, namely, 2,5-dideoxy2,5-imino-L-glycero-alpha-D-galactoheptitol and 2,5-dideoxy-2,5-imino-D-galactitol.
Keywords: alkaloids; azasugars; carbohydrates; N-H insertion; Pyrrolidines; rhodium carbenoid

Retraction: organocatalytic stereoselective synthesis of passifloricin A (Retraction of Vol 10, Pg 1820, 2012) - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2019)